The effects of solvents on the properties of ultra-thin poly (methyl methacrylate) films prepared by spin coating - Tippo, T.; Thanachayanont, C.; Muthitamongkol, P.; Junin, C.; Hietschold, M.; Thanachayanont, A. (My University, 2013)
Poly (methyl methacrylate) (PMMA) is extensively used as an insulating layer in organic electronic devices. In this study, spin coating method was used to cast thin layers of PMMA for dielectric application from solutions in three different solvents, namely dimethylformamide (DMF), n-butyl acetate and toluene. The solvent's vapor pressure causes the solvent to vaporize at different rates leading to layer's distortion and different surface roughnesses. Preparation of suitable surface morphologies, for example, pinhole-free and crack-freewas studied. A step profilometer was used to measure the film thicknesses. Alternatively an equation correlating final film thickness to spin speed and solution concentration was proposed. A metal/insulator/metal parallel plate capacitor structurewas fabricated and the current density dependence on the applied electric fieldwas measured. The resulting low surface roughness, low leakage currents, high breakdown voltage, and high dielectric constant were obtained for the 100 nm-thick PMMA film prepared with DMF. © 2013 Elsevier B.V.
Keywords: Breakdown electric field; Dielectric constant; Dissipation factor; DMF; Leakage current; PMMA; Ultrathin film